1977
DOI: 10.1148/125.3.761
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of99mTc Diphosphonate Kinetics and Bone Scans in Patients with Paget's Disease Before and After Calcitonin Treatment

Abstract: Eleven patients with Paget's disease of bone underwent serial total body bone scars before and after therapy with calcitonin. All patients studied showed improvement clinically as well as biochemically. Scan improvement was noted in patients with mild disease. Patients with severe disease showed either to change or only slight improvement on the serial bone scars The scan was of greatest value in determining the extent of disease, especially in 3 patients in whom biochemical values were normal. A single pulse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Further, management of the two conditions is different. In Paget’s disease, the tracer uptake on scintigraphy is often intense, well demarcated and evenly distributed in the affected skeleton (1,2). It tends to preserve and even enhance the normal anatomic configuration of the involved bones (3,4).…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, management of the two conditions is different. In Paget’s disease, the tracer uptake on scintigraphy is often intense, well demarcated and evenly distributed in the affected skeleton (1,2). It tends to preserve and even enhance the normal anatomic configuration of the involved bones (3,4).…”
Section: Case Reportmentioning
confidence: 99%
“…One-third of the remaining lesions are appreciated only on radiographs alone and these are either sclerotic or ‘burned out’ lesions. It has been reported that lesions detected by radiograph only were always asymptomatic whereas lesions seen on bone scintigram only were symptomatic in most patients (2). This patient had painful left hip when the second bone scan and pelvic radiograph were obtained.…”
Section: Case Reportmentioning
confidence: 99%